EFEKTIVITAS DAN PERAN GURU PAI DALAM KURIKULUM MERDEKA BELAJAR DI SMP NEGERI 1 GAMPING - HUKMA FITRIA ADIRA; MUH WASITH ACHADI (Raudhah - Proud To Be Professional, 2023)
Abstract Curriculum is the heart of education. The curriculum must continue to adapt to the times and also technology. The "Freedom to Learn" curriculum leads to ideal education, education that is ready to create and collaborate with various aspects. This type of research is qualitative research. The subject of the research was PAI teachers at SMP Negeri 1 Gamping. The technique used in determining the subject of research is purposive sampling technique. Data collection techniques with interviews and observation. The data analysis technique used was data collection, data reduction, data presentation and data conclusion. The results of the study show that the basic concept of an independent curriculum is to develop a curriculum that is better prepared in facing the advances in the technological era using Contextual Teaching and Learning (CTL) methods or learning strategies. The independent curriculum is in practice, that is, there are hours of learning projects that are carried out with other subjects to produce a work that has something to do with the Pancasila religion which upholds religious values. The independent curriculum uses a dedicated team within the school to determine the project agenda. Teachers can act as facilitators in learning-based projects that are expected to be able to make a valuable contribution to science, develop soul collaboration and also eliminate gaps in skill specifications. Teachers in increasing effectiveness can develop components whose goal is to answer the wishes of the nation who want the next generation of the nation to continue to prioritize Pancasila values. Meanwhile, there are additional Material Development related to the conditions that occur with the development of science and technology. The teacher's role in the learning process includes being a facilitator, mobilizer, and also having learning strategies and methods that can adapt to student development, infrastructure facilities and also scientific diversity that can be collaborated for example in funeral prayers there is a social dimension (morals) and also jurisprudence.